1995
DOI: 10.3109/10826089509071057
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Approaches for Older Problem Drinkers

Abstract: Recent research suggests that older adults with alcohol problems often drink in response to loneliness, depression, and poor social support networks. Although a variety of approaches such as psychodynamic, Twelve Step, social support, behavioral, and cognitive-behavioral, have been suggested, only those studies involving behavioral and cognitive-behavioral interventions have provided empirical support for treatment effectiveness. Some research also suggests that age-specific group treatment produces better out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Reactions include flushing of the face, throbbing headache, palpitations, tachycardia, nausea and vomiting. A number of studies recommend that disulfiram should not be prescribed to elderly people because of the increased risk of serious adverse effects due to physical comorbidities and polypharmacy (Dufour & Fuller, 1995;Schonfeld & Dupree, 1995).…”
Section: Drugmaintained Abstinencementioning
confidence: 99%
“…Reactions include flushing of the face, throbbing headache, palpitations, tachycardia, nausea and vomiting. A number of studies recommend that disulfiram should not be prescribed to elderly people because of the increased risk of serious adverse effects due to physical comorbidities and polypharmacy (Dufour & Fuller, 1995;Schonfeld & Dupree, 1995).…”
Section: Drugmaintained Abstinencementioning
confidence: 99%
“…In a review of psychological studies, Schonfeld and Dupree (1995) found some evidence for the effectiveness of CBT over 12-step and social support models. However, not all the reviewed studies that supported cognitive and behavioral treatment included control groups (e.g., Dupree, Broskowski, & Schonfeld, 1984).…”
Section: Alcohol Abuse and Dependencementioning
confidence: 99%
“…Older adults who misuse alcohol may drink in response to loneliness, depression, and poor social support networks (Schonfeld & Dupree, 1995). As a result, cognitive-behavioral approaches focus on improving the client's life in a variety of ways in addition to abstaining from alcohol.…”
Section: Alcohol Abuse and Dependencementioning
confidence: 99%
“…In a review of psychological interventions, Schonfeld and Dupree (1995) reported evidence for the effectiveness of cognitive and behavioral interventions over 12-step and social support models. Carstensen, Rychtarik, and Prue (1985) found that a behavioral treatment program for older males was successful in maintaining treatment gains at a 2-year follow-up.…”
Section: E Alcohol Abuse and Dependencementioning
confidence: 99%